Pengaruh Pemanfaatan Media Audio Visual Terhadap Hasil Belajar IPS Siswa Sekolah Dasar - Syafira R, Ihwal; Nawir, Muhammad; Rahman, Syarifah Aeni (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
The aim of the study was to determine the effect of the use of audio-visual media on social studies learning outcomes for fourth grade students of SD Negeri Alluka, Gowa Regency. The type of research used in this research is research with a pre-experimental design and uses a quantitative approach. Place and time of this research at SD Negeri Alluka on May 22, 2023. The research subjects used in this research were 28 grade IV students. Data collection techniques used in this study are observation, testing and documentation. The results showed that the use of audio-visual media in social studies learning had an effect on the learning outcomes of fourth grade students at SD Negeri Alluka, Gowa Regency. This can be seen in the average value of student learning outcomes before the use of audio-visual media is low at 43% and after the use of audio-visual media the average value obtained is high, namely 93% so that it can be concluded that there is an effect of using audio-visual media because it can increase social studies learning outcomes for fourth grade students of SD Negeri Alluka, Gowa Regency.